Identification and Verification of the Prodigiosin Biosynthetic Gene Cluster (BGC) in Pseudoalteromonas rubra S4059 - Xiyan Wang; Thomas Isbrandt; Emil Ørsted Christensen; Jette Melchiorsen; Thomas Ostenfeld Larsen; Sheng-Da Zhang; Lone Gram (Microbiology Spectrum, 2021)
ABSTRACT Pseudoalteromonas rubra S4059 produces the red pigment prodigiosin, which has pharmaceutical and industrial potential. Here, we targeted a putative prodigiosin-synthesizing transferase PigC, and a pigC in-frame deletion mutant did not produce prodigiosin. However, extractions of the pigC mutant cultures retained antibacterial activity, and bioassay-guided fractionation found antibacterial activity in two fractions of blue color. A precursor of prodigiosin, 4-methoxy-2,2′-bipyrrole-5-carbaldehyde (MBC), was the dominant compound in both the fractions and likely caused the antibacterial activity. Also, a stable blue pigment, di-pyrrolyl-dipyrromethene prodigiosin, was identified from the two fractions. We also discovered antibacterial activity in the sterile filtered (nonextracted) culture supernatant of both wild type and mutant, and both contained a heat-sensitive compound between 30 and 100 kDa. Deletion of prodigiosin production did not affect growth rate or biofilm formation of P. rubra and did not change its fitness, as the mutant and wild type coexisted in equal levels in mixed cultures. In conclusion, a prodigiosin biosynthetic gene cluster (BGC) was identified and verified genetically and chemically in P. rubra S4059 and a stable blue pigment was isolated from the pigC mutant of S4059, suggesting that this strain may produce several prodigiosin-derived compounds of pharmaceutical and/or industrial potential. IMPORTANCE Pigmented Pseudoalteromonas strains are renowned for their production of secondary metabolites, and genome mining has revealed a high number of biosynthetic gene clusters (BGCs) for which the chemistry is unknown. Identification of those BGCs is a prerequisite for linking products to gene clusters and for further exploitation through heterologous expression. In this study, we identified the BGCs for the red, bioactive pigment prodigiosin using genomic, genetic, and metabolomic approaches. We also report here for the first time the production of a stable blue pigment, di-pyrrolyl-dipyrromethene prodigiosin (Dip-PDG), being produced by the pigC mutant of Pseudoalteromonas rubra S4059.